Measurements of Non-reacting and Reacting Flow Fields of a Liquid Swirl Flame Burner - Chong, Cheng Tung (Chinese Mechanical Engineering Society, 2015)
The understanding of the liquid fuel spray and flow field characteristics inside a combustor is crucial for designing a fuel efficient and low emission device. Characterisation of the flow field of a model gas turbine liquid swirl burner is performed by using a 2-D particle imaging velocimetry (PIV) system. The flow field pattern of an axial flow burner with a fixed swirl intensity is compared under confined and unconfined conditions, i.e., with and without the combustor wall. The effect of temperature on the main swirling air flow is investigated under open and non-reacting conditions. The result shows that axial and radial velocities increase as a result of decreased flow density and increased flow volume. The flow field of the main swirling flow with liquid fuel spray injection is compared to non-spray swirling flow. Introduction of liquid fuel spray changes the swirl air flow field at the burner outlet, where the radial velocity components increase for both open and confined environment. Under reacting condition, the enclosure generates a corner recirculation zone that intensifies the strength of radial velocity. The reverse flow and corner recirculation zone assists in stabilizing the flame by preheating the reactants. The flow field data can be used as validation target for swirl combustion modelling.